Magnetically Separable Chiral Periodic Mesoporous Organosilica Nanoparticles - Suheir Omar; Raed Abu-Reziq (Applied Sciences, 2020)
We describe, for the first time, a successful strategy for synthesizing chiral periodic mesoporous organosilica nanoparticles (PMO NPs). The chiral PMO nanoparticles were synthesized in a sol–gel process under mild conditions; their preparation was mediated by hydrolysis and condensation of chiral-bridged organo-alkoxysilane precursor compounds, (OR‘)3Si-R-Si(OR‘)3, in the presence of cetyltrimethylammonium bromide (CTAB) surfactant. The resulting nanoparticles were composed merely from a chiral- bridged organo-alkoxysilane monomer. These systems were prepared by applying different surfactants and ligands that finally afforded monodispersed chiral PMO NPs consisting of 100% bridged-organosilane precursor. In addition, the major advancement that was achieved here was, for the first time, success in preparing magnetic chiral PMO NPs. These nanoparticles were synthesized by the co-polymerization of 1,1′-((1R,2R)-1,2-diphenylethane-1,2-diyl)bis(3-(3-(triethoxysilyl) propyl) urea) chiral monomer by an oil in water (o/w) emulsion process, to afford magnetic chiral PMO NPs with magnetite NPs in their cores. The obtained materials were characterized with high-resolution scanning electron microscopy (HR-SEM), high-resolution transmission electron microscopy (HR-TEM), energy-dispersive X-ray (EDX) spectroscopy, powder X-ray diffraction (XRD), solid-state NMR analysis, circular dichroism (CD) analysis, and nitrogen sorption analysis (N2-BET).